"It Made Me See What Kind of Teacher I Want to Be:" Critical Literacy in a Pre-service Literacy Methods Course. (2nd October 2022) - Briceño, Allison; Rodriguez-Mojica, Claudia
ABSTRACT: Drawing on critical literacy as a theoretical framework, this paper explores how a children's book writing assignment designed to center the experiences of underrepresented communities in children's literature contributed to shifts in awareness among predominantly White teacher candidates. The study occurred at a large urban university in California and included 77 participants who all participated in a required Literacy Methods course in a teacher preparation program. Teacher candidate surveys and critical content analysis of candidate-authored books revealed that candidates: (1) selected topics to write about because they had a personal connection to the issue or because of its relevance to their students; (2) created books that evidenced their ability to apply traditional literacy concepts through a critical lens, (3) evidenced a deepened understanding of representation and diversity in children's literature. Findings highlight the importance of critical literacy experiences in teacher preparation as a way to develop teacher candidates' critical lens. Implications include the importance of integrating critical literacy with traditional literacy content – it is not something "extra;" the need for a critical perspective to be an integral part of Teacher Performance Expectations and standards; and the need for ongoing professional development for both teachers and teacher educators.